A super-Earth orbiting near the inner edge of the habitable zone around the M4.5 dwarf Ross 508. (30th June 2022) - Harakawa, Hiroki; Takarada, Takuya; Kasagi, Yui; Hirano, Teruyuki; Kotani, Takayuki; Kuzuhara, Masayuki; Omiya, Masashi; Kawahara, Hajime; Fukui, Akihiko; Hori, Yasunori; Ishikawa, Hiroyuki Tako; Ogihara, Masahiro; et al.
Abstract: We report the near-infrared radial velocity (RV) discovery of a super-Earth planet on a 10.77 d orbit around the M4.5 dwarf Ross 508 ( J mag = 9.1). Using precision RVs from the Subaru Telescope IRD (InfraRed Doppler) instrument, we derive a semi-amplitude of 3.92^+0.60_-0.58\:m\:s^-1, corresponding to a planet with a minimum mass m i = 4.00^+0.53_-0.55 M_ . We find no evidence of significant signals at the detected period in spectroscopic stellar activity indicators or MEarth photometry. The planet, Ross 508 b, has a semi-major axis of 0.05366^+0.00056_-0.00049\: au. This gives an orbit-averaged insolation of ≈1.4 times the Earth's value, placing Ross 508 b near the inner edge of its star's habitable zone. We have explored the possibility that the planet has a high eccentricity and its host is accompanied by an additional unconfirmed companion on a wide orbit. Our discovery demonstrates that the near-infrared RV search can play a crucial role in finding a low-mass planet around cool M dwarfs like Ross 508.